Equitable Arabic Language Learning: An Innovative Response to Economic Challenges through the Hiwaruna Textbook - Mohammad Zainal Hamdy (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
The development of the Hiwaruna textbook was initiated as a response to the dual challenge of linguistic complexity and economic limitation faced by ibtida’ students at Darul Lugha wal Qur’an Palengaan Daja, Pamekasan. The existing textbook, Muhawarah Juz 1, was found to be linguistically demanding and economically inaccessible, creating disparities in students’ learning engagement. This study aims to design and develop a more affordable yet pedagogically sound alternative to support equitable Arabic kalam learning. Employing a Research and Development (R&D) approach based on the 4D model (Define, Design, Develop, and Disseminate), data were collected through classroom observation, teacher interviews, expert validation, and student feedback. The Hiwaruna textbook was designed to suit students’ proficiency levels, incorporating contextual themes, simplified vocabulary, visual aids, and pronunciation guides, while being printed locally at a cost 80% lower than commercial materials. The implementation demonstrated significant improvements in student motivation, comprehension, and speaking ability. Furthermore, teachers reported that Hiwaruna facilitated more interactive and inclusive classroom communication. The findings suggest that pedagogical innovation rooted in local economic awareness can enhance accessibility without compromising educational quality, offering a sustainable model for Arabic language instruction in resource-limited contexts